2002
DOI: 10.1046/j.1469-0705.2002.00643.x
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal sonography of the uterine cervix prior to labor induction

Abstract: The length of the uterine cervix, measured by transvaginal sonography, is a better predictor of the risk of Cesarean section than the Bishop score after induction of labor for medical reasons. In women with an unfavorable Bishop score, a cervical length of < 26 mm is associated with a lower risk of Cesarean section and a shorter duration of labor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
2
6

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 14 publications
4
64
2
6
Order By: Relevance
“…On the other hand, cervical length was predictive of type of delivery in patients with Bishop score ·5, but not in women with Bishop score >5, which coincide with the results of Gabriel et al [11]. Our study also showed that Bishop score failed to predict the type of delivery in the groups of women deWned by short or long cervical length (Table 1).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…On the other hand, cervical length was predictive of type of delivery in patients with Bishop score ·5, but not in women with Bishop score >5, which coincide with the results of Gabriel et al [11]. Our study also showed that Bishop score failed to predict the type of delivery in the groups of women deWned by short or long cervical length (Table 1).…”
Section: Discussionsupporting
confidence: 86%
“…However, after adjustment in a logistic regression model, only cervical length and parity were predictive of vaginal delivery. Gabriel et al [11] observed that sonographic cervical length was a better predictor of the risk of cesarean section after inducing labor than the Bishop score; they found that Bishop score 5 and cervical length 26 mm were the cut-oV points most useful clinically. In our study, the clinically most useful cut-oV points were similar to those of Gabriel et al (Bishop score 5 and cervical length 25.2 mm).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Depuis, de nombreuses études [21][22][23][24][25][26][27][28][29] ont évalué l'utilité de l'échographie transvaginale dans ce but, certaines d'entre elles trouvant que l'évaluation de la longueur du canal cervical était un facteur prédictif du succès du travail induit. Pandis et al [22] ont montré que la mesure échographique de la longueur cervicale était supérieure au score de Bishop pour prédire la durée de l'induction à l'accouchement et la probabilité d'un accouchement par voie basse dans les 24 heures.…”
Section: é Chographieunclassified
“…Dans leur étude, les patientes avec une longueur cervicale de moins de 20 mm, accouchaient toutes dans les 24 heures de l'induction par rapport aux patientes avec une longueur cervicale de plus de 30 mm (chez qui plus de 80 % restaient enceintes après 24 heures). Néanmoins, l'étude de Gabriel et al [26] apporte une nuance : si le col est favorable (score de Bishop supérieur ou égal à 5), l'étude échographique perd son avantage par rapport au score de Bishop.…”
Section: é Chographieunclassified